Global damage identification based on vibration signatures applied to masonry structures - Ramos, Luís F. (2008)
The present paper aims at damage assessment of masonry structures in an early stage. Two replicates of historical constructions were built in virgin state, one arch with 1.5 m span and one shear wall of 1 m2. Afterwards, progressive damage was applied and sequential mo-dal identification analysis was performed in each damage stage, aiming at finding adequate relations between changes in dynamical behaviour and internal crack growth. During the dynamic tests, accelerations and strains were recorded in many points of the replicates. Comparisons between different techniques based on vibrations measurements were made to evaluate which methods are the most suitable for identifying damage in masonry con-structions.